Dietary Habits and Physical Activity Affect Random Blood Sugar Levels In Outpatients - Effendi Effendi; Budhi Setianto; Agus Aan Adriansyah; Akas Yekti Pulih Asih; Difran Nobel Bistara (Jurnal Ilmiah Kesehatan, 2021)
Background: Diabetes is caused by several etiology resulting in the body not using glucose into the cells, so glucose accumulates in the blood. The pancreas cannot produce the particular hormone in type 1 diabetes. Meanwhile, type 2 diabetes is caused by the inefficient use or deficiency of certain hormones relative to blood glucose levels.  Purpose: This study analyzes the correlation between dietary regulation and physical activity and blood sugar levels in outpatients Methods: This paper was a cross-sectional analytic study. The population was all outpatients who checked their blood sugar levels at the Internal Medicine Specialist Clinic of Islamic Hospital Surabaya from January to February 2021. Meanwhile, there were 115 respondents with total random sampling. The independent variable was random blood sugar (RBS) levels, while the dependent variables were dietary habits and physical activity. Data collection used medical records at the Internal Medicine Specialist Clinic of Islamic Hospital Surabaya. Then, data analysis utilized Fisher's Exact Test with a significance of 0.05  Results: Most respondents had regular dietary habits (53%) and normal random blood sugar levels (54%). In addition, they had regular physical activity (80%), with frequency once a week (34.8%), and most types of physical activity were gymnastics (34.8%). The Fisher's Exact Test obtained p=0.000 in analyzing between dietary habits and RBG levels. In addition, p=0.000 in evaluating between physical activity and RBG levels. Conclusion: Dietary habits and physical exercise affect random blood sugar levels in outpatients. Further study should evaluate other factors associated with blood sugar levels.